2013
DOI: 10.1016/j.alcohol.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol effects on synaptic transmission in periaqueductal gray dopamine neurons

Abstract: The role of dopamine (DA) signaling in regulating the rewarding properties of drugs, including alcohol, has been widely studied. The majority of these studies, however, have focused on the DA neurons located in the ventral tegmental area (VTA), and their projections to the nucleus accumbens. DA neurons within the ventral periaqueductal gray (vPAG) have been shown to regulate reward but little is known about the functional properties of these neurons, or how they are modified by drugs of abuse. This lack of kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Furthermore, the PAG receives a significant serotonergic innervation from the DRN involved in fight‐or‐flight behavioral responses (Johnson et al., ). Li and colleagues () reported that acute ethanol produced a robust enhancement of glutamatergic synaptic transmission in the PAG. GABA A and μ opioid receptors (Silva and Nobre, ) and glutamate receptors (Ezequiel Leite and Nobre, ; Long et al., ) within the PAG are affected in ethanol withdrawal.…”
mentioning
confidence: 99%
“…Furthermore, the PAG receives a significant serotonergic innervation from the DRN involved in fight‐or‐flight behavioral responses (Johnson et al., ). Li and colleagues () reported that acute ethanol produced a robust enhancement of glutamatergic synaptic transmission in the PAG. GABA A and μ opioid receptors (Silva and Nobre, ) and glutamate receptors (Ezequiel Leite and Nobre, ; Long et al., ) within the PAG are affected in ethanol withdrawal.…”
mentioning
confidence: 99%
“…Finally, we found little to no I h current in the RLi dopamine neurons. Other groups have also found a lack of I h current in dopamine neurons with anatomical locations near the midline (Lammel et al 2011, Li et al 2013). Functionally, these properties are expected to affect differences in excitability and may influence plasticity of synaptic transmission.…”
Section: Discussionmentioning
confidence: 88%
“…Thus we analyzed the properties of these neurons in a TH-eGFP line previously utilized for analysis of dopamine neurons (Li et al 2013). In an initial characterization of the basic membrane properties of eGFP positive neurons in the RLi of these transgenic mice, we found several significant differences as compared to eGFP positive lateral VTA neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the vPAG is an additional sig nificant source of dopamine input to the BNST, and therefore interactions between these regions may con tribute to outcomes following chronic ethanol exposure. Reciprocal BNSTvPAG pathways require further inves tigation as recent evidence shows that acute ethanol exposure increases the firing rate of dopamine neurons in the vPAG, perhaps by enhancing excitatory drive onto these neurons (Li, McCall, Lopez, & Kash, 2013), which could result in altered dopamine output to the BNST.…”
Section: The Potential Role Of Reciprocal Projectionsmentioning
confidence: 99%